(3GdeNJGQ ef TYQ CHj JeGes - (3eLghds; (3CHh JeGe GdWGFj , CHh JeGe MHjH Hf ChS Hf GdMGQK GdWGFj,J (B231 (3g` s
(3ChdgG (B:s
(3ef bUjOI jeOM HgG GdeCehf(B: (3pOnef Cdqe HgG abGd SdGoe ce nMqd YbOI UHQg GdEdeGe fLRJ QcGH Gdbhe MJi JZjQhG QMdi dbO YfahG Ydqj hdGehG s
(3BNQgG (B:s
(3adjHdZ GdaJjGof Yfj eGdckG Cfj eJi jJKdehG CJgOe JeJ GdeNJGQGJ ef OjhGf CHj JeGe GdWGFj hgj Cda hSJI hSHYhf HjJkG hGdMeO ddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdNGeSs
(3HgG fXGe GdJYbjHIs
(3HBNQgG CfgG hba ef NRGfI GdEeGe GdegOj CMeO Hf GdMSfs
(3JHUQI GdYfhGf (B:s
(3GNJjGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B170s
Keywords: (3GdCOHs